2005
DOI: 10.1620/tjem.207.171
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Accelerates Pulmonary Artery Development in Neonate Rabbits

Abstract: Pulmonary vascular resistance drops sharply within a few minutes after birth for the survival of neonates. A majority of this resistance is caused by "pulmonary vascular bed" or vessel lacking smooth muscle cells. Heparin is known to promote proliferation and development of endothelial cells and to subsequently decrease their overall vascular resistance, but its detailed features remained unknown. Therefore, in this study we treated neonatal rabbits with heparin, protamine (antagonist of heparin), or saline, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…route. 26 This study showed that the intrapleural administration of 1000 IU heparin alone or in combination with 1 mg of rhDNase did not facilitate the treatment of empyema in rabbits. Intrapleural heparin significantly increased the drainage of pleural fluid compared with combination and saline groups.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…route. 26 This study showed that the intrapleural administration of 1000 IU heparin alone or in combination with 1 mg of rhDNase did not facilitate the treatment of empyema in rabbits. Intrapleural heparin significantly increased the drainage of pleural fluid compared with combination and saline groups.…”
Section: Discussionmentioning
confidence: 72%
“…In the rabbit model of thromboemboli, heparin dose usually varies between 125 and 500 UI/kg/day for i.v. route 26 …”
Section: Discussionmentioning
confidence: 99%
“…The most prominent structural change in the pulmonary vascular bed of newborn rabbits was found to be reduction in the alveolar:arteriolar ratio associated with new vessel growth, but the mechanism could not be understood. In another study [31], it was shown that UFH accelerates pulmonary artery development and decreases pulmonary artery pressure in neonatal rabbits. This fact was explained by the effect of heparin promoting pulmonary vascular proliferation and nitric oxide synthesis.…”
Section: Methodsmentioning
confidence: 99%